STUDIES ON THE ASCARIS-BACTERIA RELATIONSHIP IN MAN AND PIGLETS (1983)
The paucity of knowledge of the inter-relationship of bacteria and Ascaris stimulated this study. Very little was known about the sources of Ascaris infection in man in Ibadan. Investigations conducted on the action of intestinal bacteria on the development of Ascaris eggs to the infective stages involved the growing of fertile eggs of Ascaris lumbricoidea and Ascaris suum in diluted and undiluted overnight broth cultures of Escherichia coli, Proteus mirabilis. Streptococcus faecalis (Enterococci), Bacillus subtilis, Bacillus cereus, Pseudomonas aeruginosa, Clostridium welchii and also in sterile nutrient browth. The bacterial species used in the experiments inhibited the cleavage and development of both the human and porcine scaris eggs beyond 2-cell stage. The ovostatic action of the bacterial species on the eggs was found out to be related to respiratory processes of the actively growing and multiplying bacteria which consumed all the available oxygen from the environment of the eggs. After the removal of bacteria from cultures, the eggs developed very well. The bacterial flora of Ascaris suum and its relationship to the host flora was also investigated. The body surface of the adult worms was cultured on selective media. The different parts of the adult wornfs gut were cultured for isolation of micro-organisms. The faeces collected from pigs were also cultured. E. coli, Streptococcus faecalis, Staphylococcus aureus, Staphylococcus albus, Proteus vulgaris, Proteus mirabilis, Pseudomonas aeruginosa, Lactobacillus acidophilus, Bacillus subtilis and Candida albicans were isolated from the cultures but no anaerobic organism was isolated. The faeces cultures yielded the same genera of bacteria as in Ascaris suum adult worms, bat Clostridium welchii, an anaerobic organism was isolated from the faeces. The results showed that adult Ascaris suum can act as a vehicle of bacterial infections in ascariasis where the adult worm is active and migratory. In this case the pig bacteria which are limited in its ability to penetrate the intact epithelium of the animal can often be deposited on internal tissue by the migrating worms where untold problems could be set up. The effect of intestinal flora on the establishment, development and pathogenicity of Ascaris suum larvae in piglets was also investigated. The results have shown that development of Ascaris suum larvae to adult worms took place in the presence of a normal intestinal flora in piglets. Furthermore, the results have shown that the two agents (Ascaris suum larvae and bacterial species) worked together to produce a disease condition more severe than the sum total of effect produced by either the worm or the bacteria independently. Finally, investigations were conducted to find out sources of infection with human ascariasis in Ibadan. The results have shown that common food items like fruits, vegetables, gari and palm-wine are contaminated by Ascaris eggs and therefore could serve as sources of Ascaris infection to those people who eat these food items raw or uncooked. It was observed that the Ascaris infection could occur through contaminated fingers of egg-passers, through dust and through the activity of flies. Ascaris eggs were found on edible vegetables and fruits and this observation emphasises the need for strict observation of simple hygiene methods aimed at eliminating the Ascaris eggs before consumption of the uncooked food items.